2008
DOI: 10.1042/bj20071371
|View full text |Cite
|
Sign up to set email alerts
|

Alternative metabolic fates of phosphatidylinositol produced by phosphatidylinositol synthase isoforms in Arabidopsis thaliana

Abstract: PtdIns is an important precursor for inositol-containing lipids, including polyphosphoinositides, which have multiple essential functions in eukaryotic cells. It was previously proposed that different regulatory functions of inositol-containing lipids may be performed by independent lipid pools; however, it remains unclear how such subcellular pools are established and maintained. In the present paper, a previously uncharacterized Arabidopsis gene product with similarity to the known Arabidopsis PIS (PtdIns sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 51 publications
4
84
1
Order By: Relevance
“…One explanation could be that PIS2 is specifically expressed in developing seeds but PIS1 is not, according to the microarray data (Zimmermann et al, 2004). Another possibility is that PIS1 and PIS2 have different biochemical properties because overexpression of PIS1 did not affect PI content (Lö fke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation could be that PIS2 is specifically expressed in developing seeds but PIS1 is not, according to the microarray data (Zimmermann et al, 2004). Another possibility is that PIS1 and PIS2 have different biochemical properties because overexpression of PIS1 did not affect PI content (Lö fke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that overexpression of PIS2, driven by its own promoter plus four 35S enhancers, largely rescued the cotyledon phenotype of mips1 mips3 (Figure 10). Recently it was reported that overexpression of PIS2 in Arabidopsis increased levels of PtdIns(4)P and PtdIns (4,5)P 2 , which are the major PI species in plasma membranes, the endoplasmic reticulum, the Golgi complex, and trafficking vesicles (Lö fke et al, 2008). Therefore, these results suggest that, under myo-inositol insufficient conditions, there are limited amounts of the membrane components PtdIns and PIs, possibly PtdIns(4)P and PtdIns(4,5)P 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that mips1 mutants have altered ceramide levels, one possible explanation for the opposing resistance phenotypes of mips1 and mips2 mutants may be a difference in MIPS1 and MIPS2 impact on PtdIns and ceramide levels. Evidence exists that the two Arabidopsis PtdIns synthases channel different species of PtdIns into different physiological pools (Lofke et al, 2008); thus, metabolic channeling of myo-inositol derived from MIPS1 catalysis could be preferentially routed into PtdIns and then sphingolipid synthesis. Reduction of InsP 6 in cereal grains fed to nonruminant animals to reduce phosphorous pollution of certain watersheds has been a pressing goal of plant biotechnology (Raboy, 2007).…”
Section: Myo-inositol Synthesis and Inspmentioning
confidence: 99%
“…2) induces not only the synthesis of PI as expected, but also that of PA, and that overexpression of PIS1 induces the synthesis of phosphatidylethanolamine (PE) and diacylglycerol (DAG). 14 In addition, PIS2 is responsible of the synthesis of PI for the production of phosphoinositides, which increases with PIS2 overexpression, 14 and such production of PI by PIS2 is related with PI kinases and phosphoinositides for regulation of secretion, as shown for pectin secretion Figure 2. Simplified phospholipid biosynthetic pathways in plants.…”
Section: Rhd3 Defect In the Er Membrane Affects Phopholipid Homeostasismentioning
confidence: 99%
“…Finally, the presence of more than 20 putative sites of phosphorylation (threonine or serine) in the sequence of PIS1 may suggest possible strong regulations of PIS1 activity. 14 All these points combined to some extent could participate to the proliferation and specific morphological features of the ER in the rhd3 mutant lines.…”
Section: Rhd3 Defect In the Er Membrane Affects Phopholipid Homeostasismentioning
confidence: 99%